2003
DOI: 10.1186/1477-7827-1-27
|View full text |Cite
|
Sign up to set email alerts
|

Oolemmal proteomics – identification of highly abundant heat shock proteins and molecular chaperones in the mature mouse egg and their localization on the plasma membrane

Abstract: BackgroundThe mature mouse egg contains the full complement of maternal proteins required for fertilization, the transition to zygotic transcription, and the beginning stages of embryogenesis. Many of these proteins remain to be characterized, therefore in this study we have identified highly abundant egg proteins using a proteomic approach and found that several of these proteins also appear to localize to the egg surface. Characterization of such molecules will provide important insight into the cellular eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 55 publications
(55 reference statements)
2
21
0
Order By: Relevance
“…Despite this, the individual chaperone proteins, calreticulin, calnexin, HSPA1A, HSPA5, HSP90AA1, and HSP90B1, have been confirmed on the surface of mature mouse oocytes (Calvert et al 2003) and may act in a coordinated manner to activate fusion machinery on the surface of the oocyte. In an independent study, calreticulin has also been found to localize to the cortical granules of hamster oocytes and appears to be released into the perivitelline space following oocyte activation (MunozGotera et al 2001), raising the possibility that it is involved in the priming of oocytes in preparation for fusion with a spermatozoon.…”
Section: Molecular Chaperones In Gamete Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, the individual chaperone proteins, calreticulin, calnexin, HSPA1A, HSPA5, HSP90AA1, and HSP90B1, have been confirmed on the surface of mature mouse oocytes (Calvert et al 2003) and may act in a coordinated manner to activate fusion machinery on the surface of the oocyte. In an independent study, calreticulin has also been found to localize to the cortical granules of hamster oocytes and appears to be released into the perivitelline space following oocyte activation (MunozGotera et al 2001), raising the possibility that it is involved in the priming of oocytes in preparation for fusion with a spermatozoon.…”
Section: Molecular Chaperones In Gamete Fusionmentioning
confidence: 99%
“…Of the chaperone proteins identified on the oolemma, HSP70 is constitutively synthesized in the preovulatory mouse oocyte (Calvert et al 2003) as well as the mature bovine oocyte (Kawarsky & King 2001). Following zygotic gene activation in the two-cell mouse embryo, HSP70 is one of the primary genes to be expressed.…”
Section: Molecular Chaperones In Gamete Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPA4l is highly expressed in spermatogenic cells of testis from late pachytene spermatocytes to postmeiotic spermatids3 while HSPA4 is predominant in the testis and ovary 45. ORP150 is expressed in the plasma membrane of mature mouse oocytes 6. This expression pattern suggests a critical role for the HSP110 family proteins in reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have explored the role of maternal proteins using proteomics, including from bovine, porcine, and mouse oocyte proteomes (Calvert et al 2003, Ellederova et al 2004, Memili et al 2007, Susor et al 2007, Zhang et al 2009, Wang et al 2010. Wang et al (2010) successfully identified 2781 proteins in the germinal vesicle (GV) of mouse oocytes, 2973 proteins in meta-phase II (MII) oocytes, and 2082 proteins in zygote.…”
Section: Introductionmentioning
confidence: 99%